Discrete universality of absolutely convergent Dirichlet series - Jasas, Mindaugas; Laurinčikas, Antanas; Stoncelis, Mindaugas; Šiaučiūnas, Darius (Mathematical Modelling and Analysis, 2022)
In the paper, an universality theorem of discrete type on the approximation of analytic functions by shifts of a special absolutely convergent Dirichlet series is obtained. These series is close in a certain sense to the periodic zeta-function and depends on a parameter.